Ultraviolet light treatment of titanium suppresses human oral bacterial attachment and biofilm formation: A short-term in vitro study - Ishijima, Manabu (2019)
Antibacterial dental implants and related prosthetic components could help to reduce infection and prevent peri-implantitis. The purpose of this study was to determine the effect of ultraviolet (UV) light treatment of titanium on biofilm formation of human oral bacteria. Materials and Methods: Machineprepared commercially pure titanium disks were treated with UV light for 12 minutes. Human oral bacteria were seeded onto untreated and UV-treated disks. Early bacterial attachment to titanium was assessed at 12 hours. Surface topography of initial biofilms was evaluated by 3D scanning electron microscopy at 24 hours. The quantity and morphology of subsequent colony development and biofilm formation were examined by confocal laser scanning microscopy for up to 7 days. Results: Throughout the time course, significantly fewer bacterial cells attached to UV-treated titanium surfaces compared with untreated ones. While biofilm developed rapidly to a final thickness of approximately 16 μm by day 3 on untreated titanium, on UV-treated surfaces it remained below 8 μm, even at day 7. Similarly, UV treatment resulted in 70% less exopolysaccharide (EPS) volume than on untreated surfaces at day 7. This is consistent with the finding that EPS production per cell was significantly lower on UV-treated surfaces. Untreated titanium surfaces covered with biofilm were fivefold rougher than the original machined surface, while UV-treated surfaces remained twofold rougher due to significantly less biofilm formation. Conclusion: UV treatment of titanium surfaces significantly reduces attachment of human oral bacteria and subsequent biofilm formation as well as EPS production for at least 7 days. UV treatment prevented the escalation of surface colonization, mitigating an unfavorable bacteriophilic cascade and environmental trigger for biofilm formation.